Peran Keberadaan PT Batujaya Bersama Sejatera dalam Meningkatkan Ekonomi Sosial Masyarakat di Desa Walandano Kecamatan Balaesang Tanjung - Leni Afriani; Ayu Andira; Muh Taufik Tiaki (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2026)
This research aims to analyze the role and impact of PT Batujaya Bersama Sejahtera (PT BBS) on the socio-economic conditions of the community in Walandano Village, Balaesang Tanjung District. The background of this study is driven by the massive expansion of the mining industry in Central Sulawesi, which triggers a structural shift from traditional agriculture to an industrial economy. This study employs a qualitative method with data collection techniques including in-depth interviews, observation, and documentation. The findings indicate that PT BBS plays a significant role in local economic development by providing employment opportunities, increasing household income, and improving public infrastructure such as roads and jetties. However, the study also identifies social disruptions, including public protests regarding land issues and environmental concerns like dust and noise pollution. The implications of this research suggest that the company must strengthen its Corporate Social Responsibility (CSR) programs by focusing on sustainable community empowerment and more transparent communication to mitigate social risks. These findings contribute to the literature on regional economic development and social change in coastal mining areas.